Cytochrome P450‐2D6*4 polymorphism seminal relationship in infertile men. (27th May 2014) - Zalata, A.; El‐Samanoudy, A. Z.; Osman, G.; Elhanbly, S.; Nada, H. A.; Mostafa, T.
Summary: This study aimed to assess cytochrome (CY) P450‐2D6*4 polymorphism relationship with semen variables in infertile men. In all, 308 men were included; fertile normozoospermia (N) ( n  = 77), asthenozoospermia (A) ( n  = 70), asthenoteratozoospermia (AT) ( n  = 75) and oligoasthenoteratozoospermia (OAT) ( n  = 86). They were subjected to history taking, clinical examination, semen analysis, sperm acrosin activity, seminal malondialdehyde (MDA) and CYP450‐2D6*4 genotyping. CYP450‐2D6*4 wild‐type allele was represented in 76.5% of N, 70% of A, 66.7% of AT and 57.7% of OAT men where homozygous gene mutation was present in 5.9% of N, 20% of A, 26.6% of AT and 26.9% of OAT men, respectively. Sperm acrosin activity, sperm concentration, sperm motility, linear sperm velocity and sperm normal forms were significantly higher, and seminal MDA level was significantly lower in men with CYP450‐2D6*4 wild‐type allele compared with men with homozygous mutation. It is concluded that CYP450‐2D6*4 wild‐type allele has higher frequency where homozygous‐type allele has lower frequency in N men compared with A, AT and OAT men. Sperm acrosin activity index, sperm concentration, sperm motility, linear sperm velocity and sperm normal forms were significantly higher, and seminal MDA level was significantly lower in men with CYP450‐2D6*4 wild‐type allele compared with men with homozygous mutation.